2002
DOI: 10.1530/rep.0.1230243
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal regulation of apoptosis in rabbit granulosa cells in vitro: evaluation by flow cytometric detection of plasma membrane phosphatidylserine externalization

Abstract: Annexin V and propidium iodide bivariate analysis and the TUNEL method were used to quantify hormonal regulation of apoptosis in rabbit granulosa cells from preovulatory follicles in vitro. The aim of this study was to analyse comparatively the effects of gonadotrophins and their second messenger in the regulation of granulosa cell apoptosis in (i) cultured isolated granulosa cells and (ii) granulosa cells scraped from cultured follicles. The results showed that increasing doses of FSH had no effect on apoptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 18 publications
3
7
0
2
Order By: Relevance
“…Moreover, the proportion of apoptotic granulosa cells increased with the time of culture, which is in agreement with the findings of Maillet et al [45]. Lin and Rui [37] showed that the rate of cell apoptosis in porcine small follicles cultured for 24 hours was higher than that of cells isolated from large and medium ones, suggesting that follicular apoptosis may be regulated in a stage-specific manner.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, the proportion of apoptotic granulosa cells increased with the time of culture, which is in agreement with the findings of Maillet et al [45]. Lin and Rui [37] showed that the rate of cell apoptosis in porcine small follicles cultured for 24 hours was higher than that of cells isolated from large and medium ones, suggesting that follicular apoptosis may be regulated in a stage-specific manner.…”
Section: Discussionsupporting
confidence: 91%
“…In the porcine ovary, there are many follicles of different stages and sizes because of the lack of follicular waves, unlike domestic ruminants [45]. Apoptosis is induced in granulosa cells located in the inner surface of the granulosa layer but not in the cumulus cells and oocytes in the early stages of atresia [44], which was confirmed by data collected in our study.…”
Section: Discussionsupporting
confidence: 88%
“…In rabbits, FSH has no effect on apoptosis of isolated granulosa cells cultured in vitro (Maillet et al, 2002), whereas in rats, pigs, and cows, FSH attenuates apoptosis in cultured isolated granulosa cells in vitro (Zhang et al, 2011).…”
Section: Effect Of Fsh In Rescuing Granulosa Cells From Apoptosis In mentioning
confidence: 91%
“…The reproductive performance of any mammalian species can be enhanced by enriching nutrition, environmental factors like photoperiod, temperature, humidity, etc., through selective breeding, endocrine manipulations, and better management practices [1][2][3][4][5][6]. The development and growth of the ovarian follicles is finely regulated by a complex interaction of extracellular and intracellular factors, any deviation thereof leads to follicular atresia [6][7][8].…”
Section: Introductionmentioning
confidence: 99%